Framework for evaluating sustainably sourced renewable materials. Issue 4 (1st October 2016) - Weisbrod, A.; Bjork, A.; McLaughlin, D.; Federle, T.; McDonough, K.; Malcolm, J.; Cina, R.
ABSTRACT: To meet rising global demand of food, materials, and energy, a sustainable supply of bio-based feedstocks is needed. This paper describes a framework to assess the sustainability of bio-based feedstocks. The framework, a result of a collaboration between a consumer goods company and non-governmental organization (NGO), applies multiples methods across four principles: (1) life cycle perspective; (2) food security impact; (3) environmental and social risks; and (4) sustainability claims. The framework can be used to assess risks from production to post consumer use. A case study demonstrates the practical application of the framework within corporate procurement.